Deviations from triangular arbitrage parity in foreign exchange and Bitcoin markets - Julia E. Reynolds; Leopold Sögner; Martin Wagner (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2020)
This paper applies recently developed procedures to monitor and date so-called "financial market dislocations", defined as periods in which substantial deviations from arbitrage parities take place. In particular, we focus on deviations from the triangular arbitrage parity for exchange rate triplets from a cointegration perspective. Due to increasing attention on and importance of mispricing in the market for cryptocurrencies, we include the cryptocurrency Bitcoin in addition to fiat currencies. We do not find evidence for substantial deviations from the triangular arbitrage parity when only traditional fiat currencies are concerned, but document significant deviations from triangular arbitrage parities in the newer markets for Bitcoin. We confirm the importance of our results for portfolio strategies by showing that a currency portfolio that trades based on our detected break-points outperforms a simple buy-and-hold strategy.
Keywords: G12; G15; C22; C32; 330; Triangular Arbitrage Parity; Foreign Exchange Markets; Cryptocurrencies; Cointegration; Monitoring